Faktor-faktor Penentu Niat Membayar Zakat Melalui Platform Digital pada Masyarakat Kabupaten Karanganyar - Maliha Azahro; Mohamad Irsyad (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The realization of zakat collection which is still much lower than the existing potential indicates that zakat management has not reached the optimal level. One of the causes is the ease of access or underutilization of technology in the payment of zakat. This study aims to test and examine how the intention to pay zakat through digital platforms is influenced by performance expectations, effort expectations, social influence, and facilitating conditions. The object of this research is Muslim people aged >23 years in Karanganyar Regency. Using purposive sampling method, 101 respondents were taken as samples. In this study, data processing was carried out using SmartPLS software. The findings of the analysis show that the intention to pay zakat using digital platform is significantly positively influenced by social influence and facilitating conditions. On the other hand, intention to pay zakat through digital platform is not significantly influenced by performance expectancy and effort expectancy. This is due to the view of respondents that the benefits and usability offered and the condition of the community is no longer familiar with technology so that performance expectations and business expectations are not the main factors that encourage people to utilize digital platforms.